2012
DOI: 10.1371/annotation/7b65cf64-9fd5-4b95-baf2-8824c4785ab1
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Quantifying Killing of Orangutans and Human-Orangutan Conflict in Kalimantan, Indonesia

Abstract: Human-orangutan conflict and hunting are thought to pose a serious threat to orangutan existence in Kalimantan, the Indonesian part of Borneo. No data existed prior to the present study to substantiate these threats. We investigated the rates, spatial distribution and causes of conflict and hunting through an interview-based survey in the orangutan's range in Kalimantan, Indonesia. Between April 2008 and September 2009, we interviewed 6983 respondents in 687 villages to obtain socio-economic information, asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Those potential natural corridors shall be protected, and an artificial corridor could be added to facilitate orangutans' movement, specifically among the small forest patches (Ancrenaz et al, 2021). It was analyzed that one of the causes of the declining orangutans' population is hunting (Meijaard et al, 2011;Meijaard et al, 2012;Davis et al, 2013;Abram et al, 2015;Voigt et al, 2018;Meijaard et al, 2021). Moreover, Wich et al (2012) observed that hunting for Sumatran orangutan often occurred within lower geographical elevation.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Those potential natural corridors shall be protected, and an artificial corridor could be added to facilitate orangutans' movement, specifically among the small forest patches (Ancrenaz et al, 2021). It was analyzed that one of the causes of the declining orangutans' population is hunting (Meijaard et al, 2011;Meijaard et al, 2012;Davis et al, 2013;Abram et al, 2015;Voigt et al, 2018;Meijaard et al, 2021). Moreover, Wich et al (2012) observed that hunting for Sumatran orangutan often occurred within lower geographical elevation.…”
Section: Management Implicationsmentioning
confidence: 99%